Screening anti‐allergic components of Astragali Radix using LAD2 cell membrane chromatography coupled online with UHPLC‐ESI‐MS/MS method. (4th September 2016) - Lv, Yanni; Sun, Yueming; Fu, Jia; Kong, Liyun; Han, Shengli
Abstract: Huangqi (Astragali Radix), a traditional Chinese herb, is widely used in clinical therapy in China. In addition, an anti‐allergic effect of constituents in Huangqi has been reported in the scientific literature. In the present study, cell membrane chromatography coupled online with UHPLC‐ESI‐MS/MS method was developed to screen, analyze and identify the anti‐allergic components of Huangqi. The Laboratory of Allergic Disease 2 (LAD2) cell was used to establish cell membrane chromatography, which was combined with UHPLC‐ESI‐MS/MS. The coupled system was then used to screen anti‐allergic components from Huangqi. Effects of active components were verified by histamine release assay. A component retained on the LAD2 cell membrane chromatography was identified as formononetin. Bioactivity of formononetin was investigated by histamine release assay in LAD2 cells, and it was found that formononetin could inhibit histamine release in a dose‐dependent manner from 1 to 100 μm . The LAD2 cell membrane chromatography online with UHPLC‐ESI‐MS/MS method is an effective technique for screening the anti‐allergic components of Huangqi.